2019
DOI: 10.1016/j.ekir.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti−PD-1 Immunotherapy May Induce Interstitial Nephritis With Increased Tubular Epithelial Expression of PD-L1

Abstract: Introduction Novel anticancer therapies include anti–programmed cell death protein-1 (PD-1) and anti–programmed death ligand-1 (PD-L1) drugs. These novel medications have side effects in different organs, including the kidney. The most common adverse effect in the kidney is acute interstitial nephritis (AIN). No diagnostic criteria are available to distinguish AIN associated with anti–PD-1 therapy from other AINs. Methods Kidney biopsy specimens from patients on anti–PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 18 publications
7
63
2
1
Order By: Relevance
“…First described by Izzedine et al (18), but also reported by Mamlouk et al (17) and Cassol et al (19) in their case series, acute tubular injury was observed with only modest inflammation in a substantial proportion of cases. It is not clear that this is an immunemediated entity, as supported by the immunohistochemical findings (19). More experience is needed in the natural course of tubular injury with limited interstitial inflammation during CPIT use.…”
Section: Discussion Of Casesmentioning
confidence: 99%
“…First described by Izzedine et al (18), but also reported by Mamlouk et al (17) and Cassol et al (19) in their case series, acute tubular injury was observed with only modest inflammation in a substantial proportion of cases. It is not clear that this is an immunemediated entity, as supported by the immunohistochemical findings (19). More experience is needed in the natural course of tubular injury with limited interstitial inflammation during CPIT use.…”
Section: Discussion Of Casesmentioning
confidence: 99%
“…In patients that develop ICPi-AKI, the most common pathologic finding identified to date is AIN (10)(11)(12)19 These case series emphasize that it is reasonable to assume that AIN is the cause for ICPi-AKI in the majority of cases. Finally, in a recent multicenter study of AKI in this setting, 60 patients underwent a kidney biopsy and 93% of samples were consistent with AIN (14).…”
mentioning
confidence: 84%
“…Acute tubular necrosis (ATN) is another finding reported after biopsy in patients with ICPi-AKI (13,19). Izzedine et al (13) report ATN in five out of 12 cases and highlight that without kidney biopsy patients would have been inappropriately treated with steroids.…”
mentioning
confidence: 99%
“…This assumption, though, differs from what is observed in animal models, where the absence of immune checkpoints suffices to cause ATIN 11 . The latter is also evident in patients with no known exposure to conventional nephrotoxic therapies that have also developed ATIN 27,30 .…”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 97%
“…Clinically, patients typically present with AKI that might sometimes be oliguric, pyuria, hematuria, and proteinuria that is usually bland 2,27,31 , such as seen in other cases of classic ATIN 28 . Eosinophilia is a rare finding.…”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 99%